1994
DOI: 10.1111/j.1467-9515.1994.tb00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Production and Self‐Care: New Approaches to Managing Community Care Services for Older People1

Abstract: A lack of management theory which is relevant to human service agencies, combined with a failure to recognise the very large contribution which older people make to their own care makes it difficult to deliver supportive services. Self care by elders is divided, in this preliminary classification, into new strategies for everyday living, the reallocation of time and the avoidance of risk. Managers who understand that service users are co-producers of care and recognise the need to manage the users, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In addition, the importance of psychological well-being has also been identified, especially with regard to older people retaining a degree of personal independence and control (see Wilson 1994, Clark et al 1996a,b, 1998. However, the importance of risk and damage to psychological well-being, especially service users' sense of emotional and social well-being that could arise from different professional practices seeking to manage risk appeared to be less well researched.…”
Section: Older Peoplementioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the importance of psychological well-being has also been identified, especially with regard to older people retaining a degree of personal independence and control (see Wilson 1994, Clark et al 1996a,b, 1998. However, the importance of risk and damage to psychological well-being, especially service users' sense of emotional and social well-being that could arise from different professional practices seeking to manage risk appeared to be less well researched.…”
Section: Older Peoplementioning
confidence: 96%
“…This was often a complex and lengthy process involving issues of personal choice and the desire to retain a degree of independence and control. Wilson (1994) showed that, for many older people, deciding 'what is risky?' and whether to take a risk was often a multi-dimensional process weighing up potential costs and benefits.…”
Section: Older Peoplementioning
confidence: 98%
“…There are two aspects to this issue: outcomes and targeting. Outcome measurement is fraught with problems, not least because the co-produced nature of social care means that differences between individuals will powerfully affect outcomes and make it difficult to draw general lessons (Baldock 1997;Wilson 1994). The second aspect, which is the focus of this article, is the issue of targeting.…”
Section: Evaluating the Effectiveness Of Resource Allocationmentioning
confidence: 99%
“…In other service sectors, however, the accessibility of users may be less difficult. For instance, one can easily compare parents who co-produce in child care and parents who do not (Vamstad, 2007); or compare elderly who assist in their own care with elderly who do not (Wilson, 1994). Also, the organizational staff in these sectors usually has less power than in the case of activation services.…”
Section: Methodsmentioning
confidence: 99%
“…However, this might lead to a selection effect: the inclusion of a particular group of users -those with high levels of motivation, often well-educated, native and healthy -whereas less-equipped citizens are excluded from co-produced service delivery. In the literature, however, co-production is praised for its possibility to 'empower' vulnerable citizens (Needham, 2009;Wilson, 1994). This leads to the first empirical, descriptive sub question what are the characteristics of users involved in co-production?…”
Section: Answers To the Research Questionsmentioning
confidence: 99%